2019
DOI: 10.1111/apha.13288
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and cyclooxygenase products explain the majority of hypoxic cerebral vasodilation in healthy humans

Abstract: Aim:The role of reactive oxygen species (ROS) in human cerebral blood flow (CBF) during hypoxia is largely unknown. Additionally, it is unknown whether ROS interact with cyclooxygenase-derived signals during hypoxia to increase CBF. We hypothesized ROS inhibition would reduce hypoxic CBF, and combined inhibition of cyclooxygenase (COX) and ROS would decrease hypoxic CBF more than ROS suppression alone. Methods: We measured middle cerebral artery velocity with transcranial Doppler ultrasound in 12 healthy adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…15 While, in general, altitude acclimatization can be considered a rather rare form of environmental exposure reaction, altitude physiology helps us understand other mechanistically related pathophysiological phenomena such as hypoxic cerebral vasodilation. 16 Zhang et al recently showed how keratins may counteract pulmonary artery remodelling, a major pathophysiological event in the development of pulmonary artery hypertension, which, in turn, leads to progressively increased pulmonary vascular resistance and right heart dysfunction, 17 with potential implications for novel therapeutic approaches. 18 In a similar line, Strielkov et al described how epoxygenase-derived epoxyeicosatrienoic acids are involved in the regulation of pulmonary vascular tone, and may thus be utilized therapeutically for treatment of hypoxic pulmonary vasoconstriction and related diseases.…”
Section: Environment and Exposurementioning
confidence: 99%
“…15 While, in general, altitude acclimatization can be considered a rather rare form of environmental exposure reaction, altitude physiology helps us understand other mechanistically related pathophysiological phenomena such as hypoxic cerebral vasodilation. 16 Zhang et al recently showed how keratins may counteract pulmonary artery remodelling, a major pathophysiological event in the development of pulmonary artery hypertension, which, in turn, leads to progressively increased pulmonary vascular resistance and right heart dysfunction, 17 with potential implications for novel therapeutic approaches. 18 In a similar line, Strielkov et al described how epoxygenase-derived epoxyeicosatrienoic acids are involved in the regulation of pulmonary vascular tone, and may thus be utilized therapeutically for treatment of hypoxic pulmonary vasoconstriction and related diseases.…”
Section: Environment and Exposurementioning
confidence: 99%
“…2016), albeit prostaglandins appear to interact with reactive oxygen species to regulate CBF in hypoxia (Harrell et al . 2019). Unfortunately, no study has utilized volumetric measures of CBF to investigate the influence of nitric oxide on hypoxic cerebral vasodilatation.…”
Section: Figure Simplified Schematic Of Putative Pathways Involved Inmentioning
confidence: 99%
“…To this effect, while ‘scratching the surface’ has not yet provided clear insights into the regulation of cerebral hypoxic vasodilatation, there remains utility in interrogating the specific pathways to precisely discern the independent and interacting roles of these pathways in the control of hypoxic cerebral vasodilatation (Harrell et al . 2019).…”
Section: Figure Simplified Schematic Of Putative Pathways Involved Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating the mechanisms of blood pressure regulation was again a focus of a number of articles published in Acta physiologica in the recent year. The research on basic physiological questions and mechanism in model organisms is complemented with studies that include clinical patient data …”
mentioning
confidence: 99%